2018
DOI: 10.1128/aem.01394-18
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Bacterial and Fungal Community Shifts Exhibited in Selenium-Contaminated Reclaimed Mine Soils

Abstract: Selenium contamination in natural environments is of great concern globally, and microbial processes are known to mediate Se transformations. Such transformations alter Se mobility, bioavailability, and toxicity, which can amplify or mitigate Se pollution. To date, nearly all studies investigating Se-microbe interactions have used culture-based approaches with anaerobic bacteria despite growing knowledge that (i) aerobic Se transformations can occur, (ii) such transformations can be mediated by microorganisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 96 publications
1
25
0
1
Order By: Relevance
“…Original isolation of this strain was based on its capacity to oxidize manganese, however, the strain has also been confirmed to independently aerobically reduce Se oxyanions (Rosenfeld et al, 2017). The second strain was isolated from Se contaminated surface soils in southeast Idaho (Rosenfeld et al, 2018). To isolate this second strain, soil samples were collected in June 2015 using sterile field tools.…”
Section: Fungal Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…Original isolation of this strain was based on its capacity to oxidize manganese, however, the strain has also been confirmed to independently aerobically reduce Se oxyanions (Rosenfeld et al, 2017). The second strain was isolated from Se contaminated surface soils in southeast Idaho (Rosenfeld et al, 2018). To isolate this second strain, soil samples were collected in June 2015 using sterile field tools.…”
Section: Fungal Isolationmentioning
confidence: 99%
“…Selenium is distributed naturally around the world through volcanic activity and subsequent atmospheric circulation ( Kessi et al, 1999 ; Winkel et al, 2012 ; Tan L. C. et al, 2016 ), and high concentrations of Se are inherently found in some sedimentary rocks such as limestones and shales. Unearthing Se-containing shale beds and other geogenic rock sources through mining has been shown to release high concentrations of Se to the surface environment ( Lemly, 2004 ; Zhu et al, 2008 , 2012 ; Stillings and Amacher, 2010 ; Diehl et al, 2012 ; Khamkhash et al, 2017 ; Rosenfeld et al, 2018 ). Because Se is enriched in coal, anthropogenic activities involving coal, such as mining, processing, and combustion for electricity are especially problematic for increasing environmental Se concentrations to hazardous levels ( Dreesen et al, 1977 ; Fernández-Martínez and Charlet, 2009 ; Dai et al, 2012 ; Zhu et al, 2012 ; Santos et al, 2015 ; Schwartz et al, 2018 ; Brandt et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…На участке ¹ 3, напротив, разнообразие высших растений их жизненных форм наибольшее. Это позволяет предположить более широкий спектр и большее разнообразие форм органических веществ, в том числе легкодоступных, что, в свою очередь, отражается на структуре микробиома, в частности растет число копиотрофных микроорганизмов, к которым относится большинство представителей филы Proteobacteria (58).…”
Section: анализ корреляции -разнообразия почвенного микробиома с оснunclassified
“…the increase of toxicity, microbiology is severely affected. Several studies highlighted a decrease in microbiology richness, diversity (Rosenfeld et al, 2018;Sanchez-Castro et al, 2017), composition (Martinez et al, 2018), and biomass (Narendrula-Kotha and Nkongolo, 2017). The impacts on soil properties can persist in time and, in some cases, can be detected 20 years after mine closure (Sołek-Podwika et al, 2016).…”
mentioning
confidence: 99%